Adventist missions facing the 21st century: a reader - Dunton, Hugh (Archives of international Adventist history, 1990)
Among Adventists all around the world there is a renewed interest in missions. There is, at the same time, a feeling of powerlessness as they sense the greatness of the unfinished task. There is confusion as to their relationship to other mission agencies. There is a probing for answers to questions such as: Is there salvation outside the Christian message? What is the relationship of Christianity to culture? What is the role of the modern missionary? How does Gospel Proclamation interact with Social Action? - Contents: The changing role of missions - The Biblical basis - Strategies for missions - Two African Church histories - Women in missions - Adventist overseas missions.